Advancing Local Livestock: A Strategic Community-Based Development For Pasundan Cattle Breeding In West Java - Tsani, Ashrul; Sulistyowati, Lies; Setiawan, Iwan; Darodjah, Raden Siti (Universitas Muhammadiyah Yogyakarta, 2025)
The native Pasundan cattle breed from West Java, Indonesia, delivers essential economic and ecological benefits to the local rural communities due to their exceptional adaptability and resilience. Unfortunately, the full potential of Pasundan cattle remains untapped owing to restricted access to breeding technology, insufficient institutional support, and minimal community participation. This study investigated the key drivers of community roles and community empowerment levels in Pasundan cattle breeding in West Java, Indonesia. Using Structural Equation Modeling–Partial Least Squares (SEM-PLS) on data collected from 191 farmers in Sukabumi and Ciamis, this research examined six variables: Pasundan cattle characteristics, farmer characteristics, breeding technology, supporting institutions, community dynamics, and community roles. The findings revealed that breeding technology, farmer characteristics, and community dynamics considerably influenced community roles, while Pasundan cattle characteristics, breeding technology, and community dynamics directly impacted community empowerment levels. Community roles significantly influenced community empowerment levels. Furthermore, community roles served as a solid mediating variable, linking key factors such as farmer characteristics and breeding technology to community empowerment levels. Despite the lack of direct relevance of supporting institutions, its alignment with grassroots efforts remained essential. This study stands apart from earlier research by combining socio-economic, institutional, and technological perspectives to establish a specialized framework designed for Pasundan cattle farming needs.